Organization of Pharmaceutical Business, Drug Technology, Forensic and Clinical Pharmacy: Multidisciplinary Innovative Nanotechnologies in the Development and Implementation of New Medical Products to Medical and Pharmaceutical Practice - Shapovalov, Valentyn; Osyntseva, Alina; Shapovalov, Valerii (SSP Modern Pharmacy and Medicine, 2022)
Multidisciplinary research was conducted concerning the use of innovative nanotechnologies in the development of new drugs within the framework of organization of pharmaceutical business, drug technology, forensic and clinical pharmacy. The promising development of nanomedicine and nanopharmacy in the field of drag-design for new drugs was noted. The perspective of further scientific study of the use of nanotechnologies for the pharmacotherapy of covid, post-covid, long-covid, and comorbid disorders was proven. The possibility of creating of medical and pharmaceutical industrial parks, as well, as medical and pharmaceutical clusters for financial and economic growth on the state and regional levels were substantiated.